CHANGE OF TOTAL PROTEINS AND LOTEST PROTEINS DURING TEMPE KACANGTOLO FERMENTATION PROCESS - Nani Ratnaningsih (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2007)
Kacang tolo (Vigna unguiculata) have potency as protein source instead soybean with appropriate processing such as fermentation of tempe. The objective of research was to study the nutrient changing especially total protein and digestible protein content during fermentation of tempefrom kacang tolo. The research method was the experimental method with complete block design. Watercontent was analyzed by thermogravimetry, total protein by micro Kjieldahl, and digestible protein by in vitro method. Data were analyzed by one way anova at significant level 5 %. If there are significant different, then is followed with Duncan Multiple Range Test (DMRT). Research result concluded that water content, total protein content, and digestible protein were increasing during tempefermentation.